Stiffness regulates dendritic cell and macrophage subtype development and increased stiffness induces a tumor–associated macrophage phenotype in cancer co–cultures - Guenther, Carla (Frontiers in Immunology, 2024)
Mechanical properties of tissues including their stiffness change throughout our lives, during both healthy development but also during chronic diseases like cancer (1-4). How changes to stiffness, occurring during cancer progression, impact leukocytes is unknown. To address this, myeloid phenotypes resulting from mono-and cancer co-cultures of primary murine and human myeloid cells on 2D and 3D hydrogels with varying stiffnesses were analyzed. On soft hydrogels, conventional DCs (cDCs) developed, whereas on stiff hydrogels plasmacytoid DCs (pDCs) developed. Soft substrates promoted T cell proliferation and activation, while phagocytosis was increased on stiffer substrates. Cell populations expressing macrophage markers CD14, Ly6C, and CD16 also increased on stiff hydrogels. In cancer co-cultures, CD86 + populations decreased on higher stiffnesses across four different cancer types. High stiffness also led to increased vascular endothelial growth factor A (VEGFA), matrix metalloproteinases (MMP) and CD206 expression; 'M2' markers expressed by tumour-associated macrophages (TAMs) (5). Indeed, the majority of CD11c + cells expressed CD206 across human cancer models. Targeting the PI3K/Akt pathway led to a decrease in CD206 + cells in murine cultures only, while human CD86 + cells increased. Increased stiffness in cancer could, thus, lead to the dysregulation of infiltrating myeloid cells and shift their phenotypes towards a M2-like TAM phenotype, thereby actively enabling tumor progression. Additionally, stiffness-dependent intracellular signaling appears extremely cell context-dependent, potentially contributing to the high failure rate of clinical trials (6).